Takrifan Mal (harta) menurut sarjana Asia Barat dan implikasinya terhadap transaksi masakini - Mohamad Sabri bin Haron (Institut Kajian Rantau Asia Barat, 2010)
In the life of human being, property (Mal) cannot be avoided. As such, property is listed as one of the requirements in the context of Islamic law. In the present context and in line with the swift development of Islamic banking, discussions related to property are necessary and should to be expanded to include current products. This article tries to look at the characteristics of property as envisaged by Muslim scholars and also the current view as a benchmark that could be used to evaluate or to produce the products for the market today. Results of the study showed that definition of property is not limited to certain assets in the past, but also to anything of value determined by the current practice in the society.